2003
DOI: 10.1124/jpet.102.044107
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of 5 (and 6)-Carboxy-2′,7′-Dichlorofluorescein and Its Diacetate Promoiety in the Liver

Abstract: Hepatic disposition of 5 (and 6)-carboxy-2Ј,7Ј-dichlorofluorescein (CDF) and its diacetate promoiety (CDFDA) was studied in isolated perfused rat livers. Livers from Wistar wild-type and multidrug resistance-associated protein (Mrp)2-deficient (TR Ϫ ) rats were perfused with CDF in the presence or absence of probenecid. Probenecid decreased the recovery of CDF in bile ϳ4-fold in wild-type livers (65 Ϯ 8% versus 15 Ϯ 2% of dose over 2 h). In livers from TR Ϫ rats, CDF was not excreted into bile and probenecid d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
142
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(156 citation statements)
references
References 25 publications
13
142
1
Order By: Relevance
“…In this regard, the studies of Zamek-Gliszczynski and colleagues 57 may be informative. These studies found that 6-CFDA is rapidly hydrolyzed to 6-CF when incubated with 20% rat blood.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, the studies of Zamek-Gliszczynski and colleagues 57 may be informative. These studies found that 6-CFDA is rapidly hydrolyzed to 6-CF when incubated with 20% rat blood.…”
Section: Resultsmentioning
confidence: 99%
“…25 However, other members of the fluorescein family, such as 5(6)-carboxy-2'7'-dichlorofluorescein and 5(6)-carboxyfluorescein, are secreted into the blood by MRP3; thus, it is likely that fluorescein and fluorescein monoglucuronide also interact with this transporter. 29,30 The aim of this study was to investigate the transport of fluorescein in the liver following I/R injury by intravital multiphoton tomography, correlating these results with changes in biliary excretion, plasma concentrations, and expression of the transporters.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Fig. 3B (Meier and Stieger, 2002;Zamek-Gliszczynski et al, 2003), at the canalicular pole of hepatocytes, appear therefore to be most likely functional in HepaRG cells. Interestingly, BEI value for CF in HepaRG cells (34.4 %) was nearly identical to CF BEI value reported in sandwich-cultured human hepatocytes (BEI=34%) (Hoffmaster et al, 2004), which suggests that MRP2 is similarly active in these primary human hepatocytes and in HepaRG cells.…”
Section: Resultsmentioning
confidence: 99%